Peningkatan Kompetensi Pramuwisata Untuk Menunjang Keberlanjutan Pariwisata Lokal Berbasis Budaya di Desa Tenganan Dauh Tukad, Karangasem - I Made Minggu Widyantara; I Nyoman Putu Budiartha; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Postgraduated Community Service Journal, 2025)
Tourism in Tenganan Dauh Tukad Village, Karangasem Regency, as an ancient village characterized by the Bali Aga tradition, possesses unique cultural and traditional potentials that attract both domestic and international tourists. The local Tourist Guide Group plays a crucial role as a communication bridge and provider of in-depth cultural experiences for visitors. However, most tour guides still face several limitations, including limited foreign language proficiency (English and Mandarin), minimal training in cultural interpretation, and the absence of Standard Operating Procedures (SOPs) based on the village’s awig-awig (customary regulations). This Community Service Program (Pengabdian kepada Masyarakat [PKM]) aimed to enhance the professionalism and competence of Tourist Guide Group members through socialization and basic training activities. The methods employed included assistance in drafting SOPs, facilitating socialization sessions conducted by the local Tourism Office, and implementing basic training programs. The solutions offered to address the partners’ challenges comprised improving human resource competencies, strengthening institutional capacity, standardizing services (including SOP development), and utilizing digital technology. The outputs of this program included the development of the Tenganan Dauh Tukad Tourist Guide SOP in the form of a pocketbook, publication of an accredited community service journal article, and dissemination through mass media. Improved professionalism is expected to result in more professional and educational services, increased income for tour guides, and strengthened cultural preservation and sustainability of tourism in the traditional village.